Prognostic value and immune infiltration analyses of cuproptosis-related genes in hepatocellular carcinoma - Junjie Li; Shuoyi Ma; Yantao Zheng; Mengchen Qin; Hui Jia; Chang Liu; Yunjia Li; Guanghui Deng; Min Cai; Bin Liu; Lei Gao (Acta Materia Medica)
The role of cuproptosis, a newly discovered form of programmed cell death, remains poorly understood in hepatocellular carcinoma (HCC). This study was aimed at constructing a novel cuproptosis model for analyzing the clinical features, mutation characteristics and immune profile of HCC associated with cuproptosis-related genes (CRG), and to analyze the prognostic value of CRGs in HCC. We comprehensively evaluated HCC datasets containing clinicopathological information from The Cancer Genome Atlas and GEO, on the basis of 19 CRGs. The prognostic value of the cuproptosis-related risk score was established. Our results revealed two clusters associated with cuproptosis. Cluster B exhibited pronounced isolated innate immune cell infiltration and poor prognosis, and significant differences in prognosis and immune infiltration were observed between the groups with high and low cuproptosis risk. High copper mortality risk scores were associated with an elevated tumor mutational burden (TMB) and poor prognosis. Our findings suggest that evaluating copper-death subtypes provides insights into CRGs. Moreover, the copper mortality risk score model aids in characterizing prognosis and immune infiltration independently of the TMB.